BENTUK, FUNGSI, DAN MAKNA LEKSIKON SEDEKAH BUMI PADA MASYARAKAT KAMPUNG MENGANTI, GRESIK - Dewanto, Dewanto (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2015)
Madura Language is a regional language spoken by people for communication in Madura Island. Madura language is also used by Madura descendants who live in out of Madura as foreign regional, especially in Menganti, Gresik. Madura language is used in Menganti as daily language. The use of Madura language is implied in all activities in Java Island, especially in traditional ceremony such as thanksgiving. This research uses qualitative approach. The data in this research is obtained by survey, interview, observation and recording. The object in this research is Menganti villagers. The aim of the research are (1) the forms, function, and meaning of thanksgiving lexical, and (2) factors that had influenced ceremony of the thanksgiving. This research uses semantic lexical approach to answer the problems above about lexical for examples ancak, boyot, bumbung, labun, menyan, moncek, pesarean, petelasan, sakseh, sentono, somor, and taker.The thanksgiving lexicals above are still used till now. So, the ritual ceremony of thanksgiving is still done in Menganti villages.
Keywords: thanksgiving, semantic lexical, grave of ancestors, Madura language